Emotional intelligence and tacit knowledge management in hospitality - Spyros Avdimiotis (Journal of Tourism, Heritage & Services Marketing, 2019)
Several researchers stressed out the importance of tacit knowledge underlying the fact that it is a type of knowledge, almost impossible to articulate, codify and thus to transfer. Based on the argument of Avdimiotis (2016) that tacit knowledge could be acknowledged, acquired and transferred through employees' behavioral patterns, the present paper seeks to associate emotions- as determinant factor of behavior- with tacit knowledge management in hospitality establishments. To prove the association a quantitative research was held on a stratified sample of 128 hotel employees in Northern Greece. The research model was based on Nonaka and Takeuchi (1995) SECI knowledge transfer model and Salovey and Mayer Emotional Intelligence model. Findings indicate that both Emotional Intelligence and Tacit knowledge are strongly associated, leading to the inference that E.I. is a structural element of tacit knowledge.
Keywords: D8; D83; D91; 330; Tacit Knowledge; Emotional Intelligence; Hotel and Human Resources Management